MENINGKATKAN PRESTASI AKADEMIK MATA KULIAH MATERI FIQH MELALUI STRATEGI KOOPERATIF TIPE JIGSAW PADA MAHASISWA FAKULTAS TARBIYAH JURUSAN PGMI TAHUN 2013/2014 - Husaini, Rusdiana (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2014)
Lecture method is applied lecturers are less varied and often use the method of discussion and seminars, it can be considered to be the cause of poor performance and activity of students in learning, especially in subjects in primary Fiqh MI in the majors. Classroom Action Research is done to improve student academic achievement and activity in primary department at the Faculty of Tarbiyah fiqh MI subject matter. Hypothesis action in this classroom action research is: by implementing jigsaw cooperative strategies can increase academic achievement and student activities in learning fiqh MI Classroom. Action research was conducted on the fifth semester of university students majoring in primary education academic year 2013/2014, as many as 35 people. This research was conducted as many as three cycles, each cycle meeting.the techinics of data collection are done by observation, interview and test learning outcomes. The findings of this study is the application of cooperative strategies in primary jigsaw fifth semester student of the Tarbiyah Faculty IAIN Antasari Banjarmasin in the academic year 2013/2014 on the subject matter of fiqh MI declared a success by the results of the activities of faculty and students at the end of the cycle that is good once. The implementation strategy jigsaw cooperative learning can improve student achievement in the fifth semester in primary department Faculty of Tarbiyah IAIN Antasari Banjarmasin academic year 2013/2014 on the subject matter of Fiqh MI. There are three factors that affect the implementation of cooperative learning strategies on the course material jigsaw Fiqh MI for fifth semester Faculty of IAIN Tarbiyah Antasari Banjarmasin academic year 2013/2014, namely: 1) a lecturer in the learning activities went well and increases every cycle. 2) the activity is more active and enthusiastic student each meeting. 3) improved student learning outcomes of each meeting and has achieved Complete Standard Minimum set.